1990
DOI: 10.1002/bit.260360410
|View full text |Cite
|
Sign up to set email alerts
|

The separation of affinity flocculated yeast cell debris using a pilot‐plant scroll decanter centrifuge

Abstract: The use of a scroll decanter centrifuge for the removal and dewatering of affinity-flocculated yeast cell debris from a crude homogenate is described. Laboratory shear modulus measurements were used to compare the structure of flocculated and nonflocculated sediments and to indicate the dewatering conditions under which the sediment could be discharged from the centrifuge. The structure of the flocculated sediment was such that a dry beach could be used within the centrifuge while still being able to discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Dead-end filtration requires filter aids that risk product contamination and fouling of cross-flow membranes by cell debris, which reduces flux rates and causes protein retention. In previous work we have demonstrated that the selectivity of initial solids and contaminant removal can be increased by the use of affinity flocculation of the yeast cell wall debris with borax (3,4). Large flocs are produced that can be recovered at relatively low centrifugal forces, producing a dewatered sediment, while soluble proteins remain in the supernatant (4).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dead-end filtration requires filter aids that risk product contamination and fouling of cross-flow membranes by cell debris, which reduces flux rates and causes protein retention. In previous work we have demonstrated that the selectivity of initial solids and contaminant removal can be increased by the use of affinity flocculation of the yeast cell wall debris with borax (3,4). Large flocs are produced that can be recovered at relatively low centrifugal forces, producing a dewatered sediment, while soluble proteins remain in the supernatant (4).…”
Section: Introductionmentioning
confidence: 98%
“…In previous work we have demonstrated that the selectivity of initial solids and contaminant removal can be increased by the use of affinity flocculation of the yeast cell wall debris with borax (3,4). Large flocs are produced that can be recovered at relatively low centrifugal forces, producing a dewatered sediment, while soluble proteins remain in the supernatant (4). The underlying mechanism behind the borax (sodium tetraborate)-mediated cross-linking of yeast cell wall fragments is that boron oxyanions are able to form complexes with various polyhydroxyl compounds by reacting with 1,2 cis-diols to form cyclic esters.…”
Section: Introductionmentioning
confidence: 99%
“…Bautista et al (1986) studied the recovery of hyaluronate lyase activity after cell flocculation with flocculants and observed no losses at optimal flocculation. Bentham et al (1990) and Bonnerjea et al (1988) studied protein recovery after yeast cell debris flocculation with borax followed by centrifugation and observed minimal loss to the solid floc. Sitkey et al (1992) observed 90% protein recovery after cell flocculation with organic flocculants, but studied only optimal pH.…”
Section: Introductionmentioning
confidence: 98%
“…This suggests flocculation could be an effective treatment for the complex broth [4]. Flocculation has found extensive use in the waste water and biotechnology industries to aid in separation techniques, such as filtration, flotation, sedimentation [16], and centrifugation [17], where rate improves with the size of the suspended particles. Previous studies have shown that the addition of a polyelectrolyte flocculant results in increased permeate flux rates for the crossflow microfiltration of yeast cells [18,19], CHO cell suspensions [20] in simple media, bentonite [21], and titanium oxide in deionized water [22], but microfiltration of a complex media broth has not been examined.…”
Section: Introductionmentioning
confidence: 99%